Upcycling Post-Consumer Polystyrene Waste into Liquid Organic Hydrogen Carriers - Lee, Hyeongeon; Kim, Yoondo; Ryou, Heedo; Kim, Jihun; Oh, Daewon; Nam, Eonu; Kim, Jueun; Lee, Shinjae; Bae, Jongil; Hur, Changhun; Bae, Jong-Seong; Park, Byung Gwan; et al. (American Chemical Society, 2025)
To address the dual challenges of plastic waste management and sustainable hydrogen storage, we propose an innovative strategy to upcycle post-consumer polystyrene (PS) waste into liquid organic hydrogen carriers (LOHCs). The process involves pyrolyzing PS into aromatic monomers, primarily styrene, which are subsequently hydrogenated into cyclic hydrocarbons such as ethylcyclohexane. Dehydrogenation of these hydrogen-rich LOHCs releases high-purity hydrogen, with catalytic performance strongly influenced by the properties of supported Pt catalysts. Among various supports, Pt catalysts on nanosheet-assembled Al2O3 demonstrated superior activity and stability, attributed to a higher proportion of metallic Pt0 species, low surface acidity, and enhanced pore structures. However, polycyclic compounds in the PS-derived LOHCs led to catalyst deactivation via coke formation, necessitating a distillation step to remove these precursors. Integration of distillation, energy recovery, and LOHC recycling were shown to maintain catalyst longevity and process efficiency. Life cycle assessment and techno-economic analysis confirmed that upcycling PS waste into LOHCs offers both environmental benefits, including a negative carbon footprint for LOHC production, and economic viability, with competitive hydrogen transport costs. This work not only presents a feasible route for converting PS waste into valuable energy carriers but also contributes to advancing circular carbon strategies and the hydrogen economy.